Effect of the extract of Daigo lactic acid bacteria fermentation on the composition of the microflora and intestinal motor function in experimental dysbiosis - T. S. Popova; N. S. Tropskaya; T. V. Chernen'kaya; E. A. Kislyakova; I. G. Shashkova (Трансплантология (Москва), 2016)
In experiments on rats, the efficacy of the extract of Daigo lactic acid bacteria fermentation was investigated as the means for the prophylaxis and correction of an impaired microflora composition, and small intestine motor activity changes at dysbiosis. Experimental dysbiosis induced by a 7-day oral administration of antimicrobials (Amoxycillinum and Metronidazolum) was manifested by considerable disturbances in qualitative and  quantitative composition of the jejunum and cecum microflora. A preventive administration of Daigo prior to the exposure to antimicrobials eliminated the dysbiosis signs. Daygo administration after modeling the dysbiosis led to the recovery of intestinal motor function,normalized the numbers of conditionally-pathogenic microorganisms in a jejunum, and decreased the numbers of opportunistic microorganisms in the cecum.